2019
DOI: 10.1155/2019/7681309
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cultural Factors Leading to Suicide Attempt via Organophosphate Poisoning in Nepal

Abstract: Organophosphates are commonly used in rural, agricultural communities worldwide. Poisoning in Nepal is commonly a result of suicide attempt via ingestion with a mortality rate of 41 times higher than in the United States even after appropriate treatment. The patient discussed in this case is a 46-year-old Nepalese female with a complicated psychosocial history that presented with a suicide attempt via organophosphate ingestion. She required higher doses and greater lengths of treatment of atropine and pralidox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Recent national, as well as international studies, suggest that younger people have emerged as a high-risk age group. 1 , 5 7 Our study also showed that the mean age in years in OP poisoning cases was 31.72 (±14.068). The fact that poisoning is more common among young adults reflects their vulnerability to stress, maladjustment, and immature psychological coping mechanisms at a time of life’s major stressors.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Recent national, as well as international studies, suggest that younger people have emerged as a high-risk age group. 1 , 5 7 Our study also showed that the mean age in years in OP poisoning cases was 31.72 (±14.068). The fact that poisoning is more common among young adults reflects their vulnerability to stress, maladjustment, and immature psychological coping mechanisms at a time of life’s major stressors.…”
Section: Discussionsupporting
confidence: 69%
“…Factors like early marriages, fewer opportunities for education, domestic violence, abusive spouses, problematic love and marital relationships, and unwanted pregnancies, contribute to more suicide attempts by women. 7 , 9 , 14 , 15 According to the Nepal Maternal Mortality and Morbidity (MMM) study 2008/09, the leading cause of death among women of reproductive age was suicide, comprising 16 percent of all deaths increasing from 10.2 percent in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Recent national, as well as international studies, suggest that younger people have emerged as a high-risk age group. 1,[5][6][7] Our study also showed that the mean age in years in OP poisoning cases was 31.72 (AE14.068). The fact that poisoning is more common among young adults reflects their vulnerability to stress, maladjustment, and immature psychological coping mechanisms at a time of life's major stressors.…”
Section: Discussionsupporting
confidence: 66%
“…Check for updates poisoning is a much more common problem here as a low middle income country (LMIC) compared to more developed countries such as the United States. Worldwide there are approximately 3 million cases per year of organophosphate poisoning, which is almost uniformly from self-poisoning suicide attempts revealing a mortality ranging from 6 to 30% in LMIC [1][2][3][4].…”
Section: Case Reportmentioning
confidence: 99%
“…
CASe RepoRTCheck for updates poisoning is a much more common problem here as a low middle income country (LMIC) compared to more developed countries such as the United States. Worldwide there are approximately 3 million cases per year of organophosphate poisoning, which is almost uniformly from self-poisoning suicide attempts revealing a mortality ranging from 6 to 30% in LMIC [1][2][3][4].Suicide has now become the number one cause of unnatural death in Nepal noting 5,317 people committed suicide in the fiscal year 2017-2018 [5]. It has been reported that there are nearly 15 suicides in Nepal each day according to Nepalese police [5].
…”
mentioning
confidence: 99%